Potret Upaya Perilaku Hidup Bersih Dan Sehat (PHBS) Menuju Adaptasi Kebiasaan Baru di Kecamatan Binjai Barat Kelurahan Sukaramai - Hayati, Nur Sakinah; Hasibuan, Rapotan (Jurnal Kesehatan Ilmiah Aufa Royhan, 2020)
COVID-19 is an infectious disease caused by a newly discovered type of coronavirus. This is a new virus and a previously unknown disease before the outbreak in Wuhan, China, in December 2019. The World Health Organization (WHO) declared the corona virus a pandemic on March 11, 2020, one of the countries affected by the corona virus is Indonesia. Coronavirus disease-19 (covid-19) in North Sumatra until August 19, 2020, which has confirmed Covid-19 totaling 5,898 people, who have recovered 2,833 people and who have died as many as 260 people. There were 104 cases of coronavirus disease-19 (covid-19) in Binjai City until August 19, 2020, which had confirmed Covid-19, 28 of whom had recovered and 10 who died. Purpose To know the Portrait of Clean and Healthy Behavior Effort (PHBS) towards a new adaptation in West Binjai District, Sukaramai Village. The research method used is descriptive with a qualitative approach. Data collection techniques through in-depth interviews. Types of data are primary and secondary data from observation and documentation. The number of informants used in the study were 5 people, namely people who live in West Binjai District, Sukaramai Village with a population of 9,268 people. Results and Discussion: In this study, it was found that the West Binjai people had very good efforts towards the new normal. This is evidenced by statements from several informants and relatively low case data in Binjai City.